2009
DOI: 10.1007/s10126-009-9235-9
|View full text |Cite
|
Sign up to set email alerts
|

Culture of Explants from the Sponge Mycale cecilia to Obtain Bioactive Mycalazal-Type Metabolites

Abstract: Natural products with promising biomedical properties have been described from sponges, but the problem of supply is usually a limiting factor for their pharmacological evaluation. Mycale cecilia produces an array of metabolites containing a pyrrole-2-carbaldehyde moiety (e.g., mycalazals and mycalenitriles) that have shown activity as growth inhibitors of the human prostate carcinoma cell line LNcaP. This study shows that the culture of M. cecilia is a viable method to supply mycalazals while protecting the w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 46 publications
1
18
0
3
Order By: Relevance
“…In this scenario, previous studies have investigated the possible influence of ex situ farming on sponge synthesis of bioactive metabolites, in most cases showing results comparable to those of wild specimens (de Caralt et al, 2003;Carballo et al, 2010). Moreover, some authors have observed greater metabolite production than that found in natural populations (Klöppel et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In this scenario, previous studies have investigated the possible influence of ex situ farming on sponge synthesis of bioactive metabolites, in most cases showing results comparable to those of wild specimens (de Caralt et al, 2003;Carballo et al, 2010). Moreover, some authors have observed greater metabolite production than that found in natural populations (Klöppel et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…However, concentrations of the desired compound are usually very low [6]. Harvesting sponges from nature is ecologically and economically not a valid option because of low sponge abundance [7]. This is known as the “supply problem” [4].…”
Section: Introductionmentioning
confidence: 99%
“…Semi-closed or closed systems could enable better control over environmental conditions during culture [18], possibly allowing annual rather than seasonal culture (depending on the species) [19] but cultivation in a controlled environment is to date problematic [7]. Proper handling procedures of fragments are vital to minimize damage and allow for fast recovery [20].…”
Section: Introductionmentioning
confidence: 99%
“…Although there have been multiple efforts to synthesize (+)‐discodermolide, it has not been possible to find a route for the production of this compound at an industrial level 6, 7. A feasible alternative to solve this supply problem is the use of in situ fragment cultures (aquaculture) or in vitro tissue cultures to obtain greater biomass and higher quantities of this metabolite 8, 9. Fortunately, it was discovered that in areas of Santa Marta in the Colombian Caribbean, there is a population of D. dissoluta at shallower depths (from 12 to 25 m) and in moderate densities (scattered patches of 2–5 individuals in 50 m 2 ) 10, 11.…”
Section: Introductionmentioning
confidence: 99%